A role for palindromic structures in the cis-region of maize Sirevirus LTRs in transposable element evolution and host epigenetic response - Bousios, Alexandros; Diez, Concepcion M.; Takuno, Shohei; Bystry, Vojtech; Darzentas, Nikos; Gaut, Brandon S.

(untitled) (Genome Research, 2016)
Transposable elements (TEs) proliferate within the genome of their host, which responds by silencing them epigenetically. Much is known about the mechanisms of silencing in plants, particularly the role of siRNAs in guiding DNA methylation. In contrast, little is known about siRNA targeting patterns along the length of TEs, yet this information may provide crucial insights into the dynamics between hosts and TEs. By focusing on 6456 carefully annotated, full-length Sirevirus LTR retrotransposons in maize, we show that their silencing associates with underlying characteristics of the TE sequence and also uncover three features of the host–TE interaction. First, siRNA mapping varies among families and among elements, but particularly along the length of elements. Within the cis-regulatory portion of the LTRs, a complex palindrome-rich region acts as a hotspot of both siRNA matching and sequence evolution. These patterns are consistent across leaf, tassel, and immature ear libraries, but particularly emphasized for floral tissues and 21- to 22-nt siRNAs. Second, this region has the ability to form hairpins, making it a potential template for the production of miRNA-like, hairpin-derived small RNAs. Third, Sireviruses are targeted by siRNAs as a decreasing function of their age, but the oldest elements remain highly targeted, partially by siRNAs that cross-map to the youngest elements. We show that the targeting of older Sireviruses reflects their conserved palindromes. Altogether, we hypothesize that the palindromes aid the silencing of active elements and influence transposition potential, siRNA targeting levels, and ultimately the fate of an element within the genome.